CRITICAL REVIEW OF AL-GHAZALI'S SUFFICIENT THINKING AND ITS EXISTENCE IN INDONESIA - Abdul Hadi (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
In the digital information era such as today, where everyone can express their ideas, it is like a double-edged sword with a contradictory angle between positive and negative. Among the negative ones is the rampant doctrine of